Approaches to poverty measurement in BRICS: a reflection on economic reality (the case of Brazil, China and Russia) - Massarova, Alena; Potapenko, Maria (Bulletin of Geography. Socio-economic Series, 2018)
Poverty eradication is an urgent task set by the world community in the Millennium Development Goals. Studying the success of Brazil, China and Russia as regional leaders in reducing poverty is of great scientific and practical interest for economic geographers in terms of typological peculiarities as well as the approaches and tools used. The article highlights the main features of modern countries’ social and economic development which contributed to poverty reduction or inhibited the process in the past several decades. It reveals the similarities and differences in the approaches to poverty measurement in three BRICS countries (Brazil, China and Russia) that showed the biggest progress towards poverty eradication and presents a comparative analysis of poverty research and measurement methods used at the national level.